Student Financing - Leslie, Larry L.; National Center for Higher Education Management Systems, Boulder, CO. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1982)
Results of an investigation on ways that college students finance college costs are presented. Analysis of the literature on student financing focus on the following topics: aid recipients; particular groups, such as minorities or women; and policy questions, such as loan default rates, net prices charged, or institutions' methods of awarding student aid. A chart is provided of potential data sources concerning student financing, and the capabilities and limitations of the sources. Student financing data obtained from the National Longitudinal Surveys of 1972-1976 and the Cooperative Institutional Research Program annual survey are analyzed. The findings describe the total population in terms of student, nonstudent, nonresponse, missing data, and invalid data categories. In addition, the findings provide a time-series profile of how selected students have financed their education, and detail student net prices using two calculation methods. The four major categories of student financing data are student savings and earnings, family support, scholarships/grants, and loans. The survey data are analyzed by sex, race, socioeconomic status, parental income, academic ability, high school program, siblings in school, and institutional level and control. (SW)
Availability: National Center for Higher Education Management Systems, P.O. Drawer P, Boulder, CO 80302 ($10.00).
Sponsoring Agency: National Inst. of Education (ED), Washington, DC. Educational Policy and Organization Program.
Contract Number: 400-80-0109.
ERIC Note: Report presented as part of the Higher Education Indicators project. For related documents, see HE 017 565-567. Some tables may not reproduce well due to small print.
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Keywords: College Students; Grants; Higher Education; Income; Information Sources; National Surveys; Parent Financial Contribution; Scholarships; Student Costs; Student Employment; Student Financial Aid; Student Loan Programs; College Costs; Higher Education Indicators Projects; Numerical/Quantitative Data; Reports, Research